2017
DOI: 10.3892/ol.2017.6341
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of ZNF750 gene expression, a novel tumor suppressor gene, in esophageal squamous cell carcinoma

Abstract: Abstract. The present authors previously identified a novel candidate tumor suppressor gene, zinc finger protein 750 (ZNF750), in esophageal squamous cell carcinoma (ESCC) (1). The present study aimed to clarify the clinical significance of ZNF750 expression in ESCC. The association between ZNF750 DNA mutation status and the mRNA expression was examined by whole exome sequence analysis and quantitative reverse transcription polymerase chain reaction (RT-qPCR). The expression of ZNF750 in 76 patients with ESCC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Recently, studies have found that the expression of certain genes, such as MCT4, ZNF750, Gli1, etc. was highly related to the occurrence and development of ESCC, and they might be applied as ideal biomarkers for ESCC (Cheng et al, 2018; Nambara et al, 2017; Yang et al, 2017; Zhang et al, 2018b). In addition, the aberrant expression of a few collagen family genes has also been reported to be significantly associated with the prognosis of ESCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies have found that the expression of certain genes, such as MCT4, ZNF750, Gli1, etc. was highly related to the occurrence and development of ESCC, and they might be applied as ideal biomarkers for ESCC (Cheng et al, 2018; Nambara et al, 2017; Yang et al, 2017; Zhang et al, 2018b). In addition, the aberrant expression of a few collagen family genes has also been reported to be significantly associated with the prognosis of ESCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of cancer genes across 21 tumor types identified ZNF750 as a gene harboring many early frameshift and nonsense mutations in head and neck cancer and as the only known gene residing in a small current focal deletion in head and neck and lung squamous cancers ( Lawrence et al, 2014 ). ZNF750 has also been identified as a tumor suppressor in oral and esophageal squamous cell carcinoma ( Yang et al, 2017 ; Nambara et al, 2017 ; Hazawa et al, 2017 ; Otsuka et al, 2018 ). Studies on the clonal evolution in esophageal squamous cell carcinoma revealed that the majority of driver mutations in this cancer occurred in the tumor-suppressor genes, including TP53, KMT2D , and ZNF750 ( Hao et al, 2016 ).…”
Section: Examples Of Genes With Strong Signatures Of Positive And/or mentioning
confidence: 99%
“…In oral squamous cell carcinoma, ZNF750 inhibited cell migration, invasion, and decreased the expression of matrix metalloproteinase 28, cyclin B1 and mesenchymal marker neural cadherin [24], and also have been reported to inhibit the malignant progression by regulating tumor vascular microenvironment [9]. In addition, in esophageal squamous cell carcinoma, low expression of ZNF750 was demonstrated to be closely related to the resistance to chemoradiotherapy, positive lymph node metastasis, and poor prognosis [11,25], and downregulation of ZNF750 increased cell growth, migration, and invasion [8]. In other non-squamous cell carcinomas such as nasopharyngeal carcinomas, ZNF750 has also been shown to have an inhibitory effect on malignant tumor progression [7].…”
Section: Discussionmentioning
confidence: 99%